(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper develops a methodology to analyse various parameters of student data and predict the probability of the student, getting placed in super dream or dream or mass placement company. This is based on fuzzy logic. Fuzzy logic is an approach to computing based on "degrees of truth" rather than the usual "true or false" (1 or 0) Boolean logic on which the modern computer is based. Fuzzy logic is a form of many valued logic; it deals with reasoning that is approximate rather than fixed and exact. The applications of fuzzy logic ranges from control theory to artificial intelligence. Fuzzy logic will normalise a data set and give values between 0-1. In intelligent student analysis, we normalise the student data and then analyse the normalised data. Analysis completely depends on the data set. In this case, we are dealing with student data where the data set will include student CGPA, Branch and Attendance. With which, we calculate the possibility of placement of the particular student. Techniques and system model are elaborated in this paper.